MAQSUD SHAIKHZODA'S SKILL IN USING SYNONYMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article reflects on the linguistic features of synonyms Maqsud Shaikhzoda's skill in using synonyms. Some considerations have been expressed on the role of syntactic tools in the formation of the aesthetic influence of Maqsud Shaikhzoda's poems and on the linguistic aspects of synonyms found in his poems.